Developing a module structure in an online course for LSP teacher professional development - Jurkovič, Violeta; Podgoršek, Saša (Glottodidactica, 2025)
Self-directed open educational resources can serve as valuable tools for the continuing professional development of LSP teachers. This paper introduces an open educational resource, the LSP-TEOC.Pro course, which has been available since 2023. The course is organised into instructional modules, each serving as a distinct learning block. However, a research gap remains in understanding how intra-module design influences user experience and learning outcomes in self-directed courses. Given that module structure is of utmost importance for efficient learning, the main objective of this paper is to provide an intra-module presentation and analysis from the user perspective with respect to the following elements: difficulty, length and pacing, objectives, development and sequencing, interior feature strands, design, and clarity. The qualitative data were derived from the diaries kept by the course users when engaging with course content, and the open-ended questions in the post-participation surveys completed by the users. The results of the qualitative data analysis concerning module structure revealed overall user satisfaction with the intra-module structure. However, the results also highlight several points for consideration when designing self-directed courses, particularly concerning module design and clarity, efficient use of digital tools, and the users’ needs for feedback and a sense of belonging to a community of practice. These results may assist LSP teacher educators in the application of the LSP-TEOC.Pro course in in-person, blended, or online educational events, as well as course designers of self-directed courses in reflecting on various aspects of structure at the level of individual instructional blocks.